The Encyclopedia of Female Pioneers in Online Learning, 2023. - Diane P. Janes (The Canadian Network for Innovation in Education (CNIE), 2023)
The Encyclopedia of Female Pioneers in Online Learning by Drs. Susan Bainbridge and Norine Wark is an overview of the work and experiences of 30 women - early adopters of online (OL) and distance education (DE) in their countries (although even they struggle with what to call their focus of study and practice, as discussed in Chapter 32). Building on the use of "...career profiles, original interviews, and research analysis..." (p. 1), the book is a testament to the space that women in this field, have occupied and continue to occupy in the modern-day world of technology enhanced global education. The book is divided into two parts.